Global urbanism : Knowledge, Power and the City - Lancione, Michele; Mcfarlane, Colin; Lancione, Michele; Mcfarlane, Colin (Taylor & Francis, 2021)
Eastern Europe, activism, housing, urban policies, urban power structures, spacial justice, global urbanism
English
Keywords: Urban communities; Human geography; Society & culture: general; Eastern Europe, activism, housing, urban policies, urban power structures, spacial justice, global urbanism